Genetic Analysis of Glycoprotein Gene of Indonesian Rabies Virus - Heru Susetya; Ito Naoto; Makoto Sugiyama; Nobuyuki Minamoto (Universitas Gadjah Mada, 2005)
The amino acid sequences of the Glycoprotein gene (G gene) of field rabies virus SN01-23 from Indonesia was determined. This isolate showed homology of 93% in the ectodomain of the Glycoprotein gene to that of the RC-HL strain, which is used for production of animal vaccine in Japan. The high identity in the ectodomain between this field isolate and strain RC-HL suggest that the rabies animal vaccine used in Japan will be effective for rabies street viruses in Indonesia. Result of phylogenetic analysis using the nucleotide sequences of the G genes of rabies street viruses showed that SN01-23 from Indonesia is more closely related to a rabies virus from China than to viruses from Thailand and Malaysia. This genetic data and historical background suggest that rabies viruses in China had been transferred to Indonesia through dogs brought by humans migrating from China to Indonesia.